PENGGUNAAN BAHASA ILMIAH PADA PENULISAN SKRIPSI: PROBLEMATIKA DAN ALTERNATIF SOLUSINYA (Studi Kasus Mahasiswa Jurusan Pendidikan Agama Islam IAIN Syekh Nurjati Cirebon) - Tati Sri Uswati (Jurusan Tadris Bahasa Indonesia, 2015)
Thesis is the final project of writing for students as one of the important document that represents the prestige of the institution. There are still many errors or incompatibility with the principles of the scientific diversity of languages in the thesis. Therefore, research needs to be done about it. This study aims to: 1) describe the use of scientific language on the writing of students of Department of Islamic Education IAIN Syekh Nurjati Cirebon, 2) describes the types of errors using scientific language in the thesis of the department, 3) fix the mistakes the use of scientific language, and 4) writing scientific language to describe the problems and alternative solutions. Data were taken randomly by 20% (24 thesis) of a total population of 120 thesis. The method used is descriptive qualitative. Based on the analysis of data errors, word formation found 31 errors, 61 errors word choice, sentence drafting error 62, 11 arrangement error of reasoning, and the application of rule 105 spelling errors. In addition, there are eight abstract by writing clauses ended up using the same words, but a matter of a different percentage. There are also eight title essay that begins with the word influence.